Understanding the impacts of lockdown and work disruption: A dematel based model - Jankin, Abdul Rahman; Izzati Eliana, Ishak; Lee, Chia Kuang (Penerbit Universiti Malaysia Pahang, 2024)
Almost every construction activity has been affected by the impact of COVID-19. Many construction workers were laid off during the Movement Control Order (MCO) due to lockdowns and the closure of all construction sites. In light of these circumstances, this study aims to investigate the impacts of lockdowns and work disruptions due to COVID-19, as well as explore potential strategies to overcome these impacts. Literature review efforts identified a range of potential impacts. Following a process of synthesis, six key impacts were identified for further analysis. The Decision-Making Trial and Evaluation Laboratory (DEMATEL) technique was used to examine the causal relationships between the impacts based on the pairwise rankings of 15 construction professionals in the construction industry. The findings suggest that a shortage of skilled labor (A), insufficient supplies and material delays (E), and project deceleration (D) emerged as the most critical impacts. The study proposes several strategies to mitigate these critical impacts, aiming to assist key stakeholders in both the government and construction sectors in developing effective interventions to address the consequences of lockdown and work disruption during a severe pandemic.